The Utilization of Video Makers in Essay Writing: A Case of English Education Study Program at Sriwijaya University - Sofendi, Sofendi; Putri, Ermalati; Inderawati, Rita (Jurnal Pendidikan Progresif, 2023)
The Utilization of Video Makers in Essay Writing at English Education Study Program of Sriwijaya University. Objective: The aim of this study was to discover the fifth-semester students’ views on the use of video makers in essay writing at English Education Study Program of Sriwijaya University. Method: This study applied descriptive qualitative method. There were 39 participants who participated in answering the questionnaires of this study. The data was presented and described based on the percentage obtained from the result of the questionnaires. Finding: The results of this research showed that using video makers in essay writing has a beneficial impact on students’ multimodality writing in the twenty-first century. Conclusion: Along with the advancement of technological tools, students of the 21st-century can create multimodal composition of video essays by utilizing video maker application in project-based multimodal essay writing.Keywords: 21st-century era, project-based learning, essay writing, video makers, multimodal composition.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202356